Pengaruh Hubungan Dagang Terhadap Pertumbuhan Ekonomi: Studi Kasus Indonesia dengan China - Siti Nuraysiah L; Ali Anis (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2021)
This study examines the impact of trade relation between Indonesia with China on Indonesian economic growth by using dependen variabel as net-eksport, exchange rate, and money supply start from the periode 1990 to 2019. The result analiysis by using Multiple Linear Regression obtained that: (1) Net-eksport has a negative and significant effect on Indenesian economic growth with significance of 0.0394; (2) Indonesian exchange rate against the US$ has negative and significant effect on Indonesian economic growth with significance of 0.0240; (3) Indonesian money supplay has positive and not significant effect on Indonesian economic growth with significance of 0.2576; (4) Based on the resaults of the test simultaneous effect independent variabel on dependent variabel then the result is, simultaniously varibel net-ekspor, kurs and money supply has significant on Indonesian economic growth as 46%.